Bentuk Kecerdasan Interpersonal Anak Ditinjau dari Bimbingan Orang Tua - Chasanah, Uswatun; Purbasari, Imaniar; Ismaya, Erik Aditia (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study has a background regarding interpersonal intelligence in fifth grade children at SDN 6 Jekulo, it was found that there were children who were less able to interact socially. Interpersonal intelligence is needed by children in the current era because it has something to do with their social environment, so parents who are the main education for children must be able to provide guidance to develop interpersonal intelligence in children. This study aims to narrate the form of interpersonal intelligence of children based on parental guidance methods. This study used a narrative qualitative research method which was conducted at SDN 6 Jekulo and parents' homes in March 2023 by collecting data from the results of two interviews with four children in grade V and their parents and observations for one week. Implementation of data collection is done by seeking information about the form of interpersonal intelligence of children and methods of parental guidance. The results of this study indicate that the form of interpersonal intelligence of children who receive more than one parental guidance method is said to be quite good, while the form of interpersonal intelligence of children who receive only one parental guidance method is said to be poor. Therefore, the level of interpersonal intelligence of children can be seen from the guidance methods provided by their parents.